Rechargeable scalp massager brush / Nur Bazilah Fatini Mohd Azmi ... [et al.] - Mohd Azmi, Nur Bazilah Fatini; Mohd Ariffin, Nur Ainin Sofia; Abd Manap, Siti Sarah Asyiqin; Anuar, Nur Aini Syahirah; Mohamad Norizan, Nur Nadzlinda (2023)
Personal care and hair hygiene is one of the crucial things in our daily life. Clean and hygienic hair care routine will ensure people have clean and healthy hair as well as scalp. Nowadays, most people have been investing in their personal hair care and hygiene. For example, they use some hair care tools like scalp massager shampoo brush to maintain their healthy hair as well enhance their scalp health. It cannot be denied that there are many advantages of scalp massager shampoo brush. Nevertheless, manual scalp massager does have some drawbacks such as inconsistency in pressure and movement of brush since people need to use it manually by hand. Thus, our company, BrushCraft & Co. has introduced our own Rechargeable Scalp Massager Brush. Our product is different from other traditional scalp massage brushes as it was adapted with many interesting features that will surely give satisfaction to our customers. Some of the features of our Rechargeable Scalp Massager Brush are detachable scalp massager brush, built-in shampoo dispenser, USB socket, speed control button and on-off button. The brush is made up from soft, silicon bristle, detachable and able to vibrate for massage effects. Apart from that, there is a built-in shampoo dispenser at the handle of the brush. Next, there is a speed and on-off button at the side of the brush. There is also a USB socket at the side of those two buttons. All these features will surely give such satisfaction for our customers as they are able to experience new things in their hair care routine. Moreover, our team also conducted a survey by using the Google Form. Therefore, our company can make our customers’ awareness about the existence of our product, their preferences and will on trying our products and more. According to the survey, 73.6 % respondents had never heard about rechargeable scalp massager brush before. However, among the respondents, 39.6 % are likely and 45.3 % most likely to try a new product that combines a scalp massager brush with built-in shampoo dispenser. Therefore, we will keep on improving the design and quality of our products that align with our customers’ preferences through the feedback from our beloved customers.